2016
DOI: 10.1186/s11556-016-0166-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of recovery in older patients hospitalized with different diagnoses and functional levels, evaluated with and without geriatric assessment

Abstract: BackgroundThe objective of the present study was to investigate 1) the role of different admission diagnoses and 2) the degree of functional loss, on the rate of recovery of older patients after acute hospitalization. Furthermore, to compare the predictive value of simple assessments that can be carried out in a hospital lacking geriatric service, with assessments including geriatric screening tests.MethodsProspective, observational cohort study, including 961community dwelling patients aged ≥ 70 years, transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…We found 29 studies on factors related to recovery of internal medical patients; 19 of these were prospective cohort studies [ 27 , 29–37 , 39 , 40 , 42 , 45 , 48–53 ], eight retrospective [ 28 , 38 , 41 , 43–47 , 50 ] and two used mixed methods, combining a cohort study with interviews or a survey [ 25 , 26 ]. The sample size varied from 100 [ 27 ] to over 60,000 [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…We found 29 studies on factors related to recovery of internal medical patients; 19 of these were prospective cohort studies [ 27 , 29–37 , 39 , 40 , 42 , 45 , 48–53 ], eight retrospective [ 28 , 38 , 41 , 43–47 , 50 ] and two used mixed methods, combining a cohort study with interviews or a survey [ 25 , 26 ]. The sample size varied from 100 [ 27 ] to over 60,000 [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Over the course of the study, it was observed that the frequency of delayed surgical recovery increased significantly in the control group. Studies consider that older adults have an increased chance of complications in the postoperative period, with rates ranging between 24.0% and 67.7% (Abrahamsen, Haugland, & Ranhoff, ). Our findings confirm estimates from the National Cancer Institute, which describe a higher incidence of colorectal cancer (the leading cause of colectomy) and gastric cancer (the leading cause of gastrostomy) in patients over 60 years (World Health Organization, ).…”
Section: Discussionmentioning
confidence: 99%
“…The studies demonstrated that patients treated in nursing homes suffer both from cognitive impairment (cognitive disorders were diagnosed in 67% of patients) and an inability to perform activities of daily living (ADL) (reported in 56% of patients) [ 11 ]. The Barthel Index (BI) has been used to assess the level of patient independence in daily living [ 12 , 13 , 14 ]. BI was developed as an instrument to assess the disability of patients suffering from nervous and musculoskeletal diseases receiving in-hospital rehabilitation treatment [ 15 ].…”
Section: Introductionmentioning
confidence: 99%